Optimalisasi Potensi Zakat Untuk Lembaga Pendidikan Formal Melalui Pendampingan Tata Kelola di Laziznu Kecamatan Wonodadi Blitar - Siswahyudianto, Siswahyudianto; Shobir, Labib Muzaki (Apik Cahaya Ilmu, 2025)
Most zakat funds are allocated for social and humanitarian needs. However, some educational institutions that receive zakat assistance report improvements in facilities and educational quality, such as building renovations, provision of teaching materials, and improved school operations. The guidance on zakat management provided by LAZIZNU has proven effective in raising awareness among educational institutions about the importance of transparent and accountable zakat management. However, there are some challenges in managing and distributing zakat in a way that's more focused on the education sector. This study suggests that there's a need to improve the zakat management system and tighten monitoring so that zakat can be used to its full potential to improve the quality of education in Wonodadi Blitar District..